Maize nutritional quality dataset - Bolo, Peter Omondi; Maguta, Job Kihara; mutambu, dominic mwanzia; Kinyua, Michael Wanjohi (2023)
Metadata for maize nutritional quality. Methodology: This data was mined/extracted and collated from the values reported in different published studies. The studies were qualified for inclusion in the dataset after meeting certain criteria. Some of the guidelines for inclusion were that; the study was conducted under field but not greenhouse conditions, study must have reported controls and treatments considered, study reported on maize crop, among other criteria.